PROPUESTA ESTRATEGICA UNIVERSITARIA PARA EL DESPLIEGUE DE LOS EMPRENDIMIENTOS EMPRESARIALES SOSTENIBLES: CASO CANTÃ“N RIOBAMBAECUADOR - Erazo, FlorÃpes del RocÃo Samaniego (European Scientific Journal, ESJ, 2015)
The intervention of the university acting as liaison between the local and national government and big and middle business with the community are strategic elements in contributing to the development of sustainable entrepreneurship, entrepreneurship as seen in the broader context begins in formal education and is accentuated in university. For these reasons, this paper aims to present the results of a strategic proposal from the intervention of an expert group.